2019
DOI: 10.1016/j.earlhumdev.2019.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Three-hourly feeding intervals are associated with faster advancement in very preterm infants

Abstract: Objective: To compare the effect of two-hourly (Q2H) vs. three-hourly (Q3H) feeding on time to achieve full enteral feeding, growth metrics and respiratory tolerance in very preterm infants with birth weight ≤1,250g. Study Design: Retrospective study review of 18 months before and after a change in our feeding guideline from Q3H to Q2H feedings. Results: 113 infants were included, 59 in Q3H and 54 in Q2H groups. Q2H infants required 10% more days to achieve full enteral feeding, however it was not statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Seven studies were included in the qualitative analysis. [2][3][4][9][10][11][12] The list of studies excluded following a detailed review, including the reasons for exclusion, are provided in ►Supplementary Material B (available in the online version). Of the seven studies included, four were RCTs 2,3,10,11 and three were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies were included in the qualitative analysis. [2][3][4][9][10][11][12] The list of studies excluded following a detailed review, including the reasons for exclusion, are provided in ►Supplementary Material B (available in the online version). Of the seven studies included, four were RCTs 2,3,10,11 and three were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven studies included, four were RCTs 2,3,10,11 and three were retrospective cohort studies. 4,9,12 The risk of bias for observational studies is presented in ►Table 1 and that for RCTs in ►Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A three-hourly feeding schedule can overcome the problems of both mothers and nurses, and potentially offer an advantage of faster feed advancement. 10 Physiological studies indicate that increasing the feeding interval to 3 hours may lead to better gastric emptying and less risk of feed intolerance. 1 2 However, three-hourly feeding regimes are not commonly practised in preterm infants, due to concerns about hypoglycaemia and feed intolerance.…”
Section: Available Knowledge and Rationalementioning
confidence: 99%
“…Due to the lack of scienti c basis for a two-hourly feeding schedule and perceived advantages of extended feeding schedules, three hourly feedings have been used successfully without any adverse effects [6][7][8]. Some studies observed that three hourly feeding schedules might help achieve full enteral feeds earlier, therefore, decreasing the duration of parenteral nutrition and central venous catheter [6]. A previous systematic review concluded that low-quality evidence shows that the three-hourly feeding schedule is safe and helps regain birth weight earlier than a 2-hourly feeding schedule [9].…”
Section: Introductionmentioning
confidence: 99%